Review of Adaptive Cruise Control System - Rakesh Poorella; Sai Kumar Reddy; Charanjeet Singh (International Journal of Advanced Control and System Engineering, 2023)
New technologies are constantly being created in the modern era of the automotive industry to increase driver comfort and safety. The vehicle industry is focused on creating new designs that prioritize comfort and safety to overcome this problem. The technology which helps the automotive industry is the Adaptive Cruise Control system (ACC). The ACC system is an electronic device that assists drivers to keep a guarded distance from the upcoming vehicle by automatically adjusting the vehicle's speed. It works on sensors and radars which are the heart of the system. The implementation of this system can significantly reduce the risk of accidents caused by the driver's inability to keep a safe space from the moving car ahead. The use of this technology provides a basis for additional studies concerning automotive safety and automation. In this review paper, we have explored the different technologies and mechanisms associated with ACC and their performance metrics have also been put there of.
Keywords: Adaptive cruise control (ACC); FLCs; metrics; radars; sensors